Freedom Train: The Underground Railroad as a Model of Christian Education, Antiracism, and Human Rights Advocacy - Fears, Barbara A. (Religious education, 2017)
The Underground Railroad is the first racially integrated civil/human rights movement in the United States. The basic concepts of escape and travel that undergird the movement offer a way of envisioning the teaching/learning exchange as leaving behind unhealthy ideologies, and as journeying with students from one place of understanding to another. The primary participants and select aspects of the movement also offer a way of understanding teaching/learning in the classroom. Benefits of religious educational programming utilizing the proposed model include: developing awareness of the interrelatedness of race/racism/religion/power and a countercultural, counterhegemonic perspective that is informed by faith and evidenced by praxis.